FIBERS USED IN FIBER-REINFORCED CONCRETE: TYPES, PROPERTIES, AND PROSPECTS OF PVA FIBERS - Mukhammadiyev , Nematjon; Mukhammadrasulov, Xasanjon (Techscience uz - Topical Issues of Technical Sciences, 2025)
In modern construction practice, despite the high compressive strength of cement concrete, its low tensile strength and brittle behavior lead to cracking problems in structural elements. One of the most effective approaches to overcoming these shortcomings is the use of dispersed fiber reinforcement. This paper presents a systematic review of the physical and mechanical properties, advantages, and limitations of the main fiber types used in fiber-reinforced concrete, including steel, glass, polypropylene, and basalt fibers, based on an analysis of the relevant scientific literature. Special emphasis is placed on polyvinyl alcohol (PVA) fibers, with particular attention to their chemical origin, degree of hydrolysis, interaction mechanisms with the cementitious matrix, and crack-bridging behavior. Based on the micromechanical approach developed by Victor C. Li, the role of PVA fibers in the development of high-ductility engineered cementitious composites (ECC) is substantiated. Furthermore, a comparative analysis highlights the advantages of PVA fibers over other fiber types, and the prospects for applying PVA fiber-reinforced cementitious composites in transportation, hydraulic, and industrial construction under the climatic and service conditions of Uzbekistan are discussed. The research findings indicate that PVA fibers represent a promising reinforcing component for the development of high-performance and durable concrete composites.